Traditional culture of Kazakhs of the Zhetysu and the East in photo documents (according to the album of Leibin and Bulgakov) (Journal of history, 2023)
«Regional ethnography of the Kazakh people» as a branch of the science of historical ethnography defines the features formed by the traditional culture and way of life of Kazakhs settled in different regions, based on their efforts to manage the economy, and research in this direction is of great importance. In this regard, traditional Kazakh farms, material culture, including housing, household goods, clothing, national games, musical instruments, periodic settlements, and a traditional transport system have developed in one region for centuries. Photo registrations created in historical epochs represent a number of valuable exhibits from archival documents and museum collections. On the basis of ancient photographic documents, according to the cultural landscape of the area, the features of the development of periodic settlements and pastures, the household plot, the order of movement, historical and ethnographic reconstruction of  the nomadic styles are especially important. Of great importance for the national ethnological science is the study of indigenous ethnographic concepts and categories from a scientific and practical point of view on the basis of photo data reflecting the regional specifics of the South-East, the Eastern region, which we take as an object of research. In the historical ethnography of the Kazakhs of the southeastern and eastern regions selected for study, some photographic documents indicate those cultural artifacts that have undergone changes or vanished in the light of the «combination of the traditional period and today's transformed societies».The purpose of the article is to analyze the albums of Leibin and Bulgakov as a source of the traditional culture of Zhetysu and the Kazakhs of the East.Keywords. Leibin's album, Bulgakov's album, regional ethnography, photo registration, visual ethnosource.